Total Synthesis and Anti-inflammatory Activity of Stemoamide-Type Alkaloids Including Totally Substituted Butenolides and Pyrroles - Soda, Yasuki; Sugiyama, Yasukazu; Sato, Shunsei; Shibuya, Kana; Saegusa, Junya; Matagawa, Tomoe; Kawano, Sayaka; Yoritate, Makoto; Fukaya, Keisuke; Urabe, Daisuke; Oishi, Takeshi; Mori, Kento; Simizu, Siro; Chida, Noritaka; Sato, Takaaki (Synthesis, 2022)
Totally substituted butenolide including two tetrasubstituted olefins is a distinct structural motif seen in Stemona alkaloids, but efficient methods for its synthesis are not well developed. As an ongoing program aimed at the collective total synthesis of the stemoamide group, we report a stereodivergent method to give either (E)- or (Z)-totally substituted butenolide from the same intermediate. While AgOTf-mediated elimination via an E1-type mechanism results in the formation of the kinetic (Z)-tetrasubstituted olefin, subsequent TfOH-mediated isomerization gives the thermodynamic (E)-tetrasubstituted olefin. The pyrrole ring is another important structure found in Stemona alkaloids. The direct oxidation of pyrrolidine rings with MnO2 and careful purification gives the pyrrole groups without isomerization of the stereocenter in the lactone group. These two methods enabled us to synthesize a series of stemoamide-type alkaloids including tricyclic, tetracyclic, and pentacyclic frameworks. The anti-inflammatory activities by inhibition of iNOS expression in macrophage cell line RAW264.7 indicate that the most potent anti-inflammatory compounds without cytotoxicity are protostemonines, which consist of pentacyclic frameworks including the totally substituted butenolide.
Keywords: amides; anti-inflammatory agents; butenolides; DFT calculations; iNOS; pyrroles; Stemona alkaloids; total synthesis